Every breath you take: Laser absorption spectroscopy allows unprecedented focus on the air we breathe. Issue 2 (3rd April 2023) - Naples, Mark
Abstract: ESG. Three small letters perhaps, but they are having a huge impact on science, industry, and everyday life. In industries that operate in hazardous environments, such as oil and gas mining and refineries, those letters stand for much more than environmental, social, and governance policies. They represent a framework around which an entirely new operational structure must be built, changing every level of a business from the top down.